Experimental Drugs for the Treatment of Hepatitis D - Sandmann L; Cornberg M (Dove Medical Press, 2021)
Lisa Sandmann,1 Markus Cornberg1,2 1Department of Gastroenterology, Hepatology and Endocrinology, Hannover Medical School, Hannover, Germany; 2Centre for Individualised Infection Medicine (CiiM), Helmholtz Centre for Infection Research, Braunschweig, GermanyCorrespondence: Markus CornbergHannover Medical School, Department of Gastroenterology, Hepatology and Endocrinology, Carl-Neuberg-Str. 1, Hannover, 30625, GermanyTel +49511 532 6821Email cornberg.markus@mh-hannover.deAbstract: Chronic hepatitis D virus infection is the most severe form of viral hepatitis. Antiviral treatment is urgently needed to prevent patients from developing end stage liver disease or hepatocellular carcinoma. Treatment options were limited to off-label use of pegylated interferon alfa until conditional approval of bulevirtide by the EMA (European Medicines Agency) in July 2020. However, several other antiviral compounds are currently investigated and represent promising agents for the treatment of chronic HDV infection.Keywords: hepatitis delta, HBV/HDV coinfection, interferon, bulevirtide, lonafarnib